2022
DOI: 10.14505/jemt.v13.2(58).02
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Synergies in Developing Smart Tourism Destination. A Phenomenographic Study

Abstract: This study aims to investigate the stakeholders' synergies in realising smart tourism destination. This study uses a qualitative method with a phenomenography approach. We adopted stakeholders' theory to valued stakeholder roles and perception in pursuing sustainability, competitiveness and managing smart tourism destination in Wonosobo, Indonesia. In-depth interviews with five main stakeholders' namely local government, media, tourism business, tourism community, and travel bloggers followed by three phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…Synergy between stakeholders when implementing smart tourism Hidayah et al (2022) argues that cooperation in smart tourism destination development should occur between internal stakeholders, e.g. tourism and hospitality companies (i.e.…”
Section: Smart Tourism and Stakeholdersmentioning
confidence: 99%
See 4 more Smart Citations
“…Synergy between stakeholders when implementing smart tourism Hidayah et al (2022) argues that cooperation in smart tourism destination development should occur between internal stakeholders, e.g. tourism and hospitality companies (i.e.…”
Section: Smart Tourism and Stakeholdersmentioning
confidence: 99%
“…The following six categories are subordinate to the four dimensions: cooperation leadership and government compactness (partnership); government involvement; knowledge of the development of smart tourism and human resources (human capacity) and tourism business competitiveness. The micro-environment, which includes social and cultural conditions and the macro-environment of the destination, including technologies, ecology, economic and political conditions, are also likely to influence the pace of smart tourism adoption in the future (Hidayah et al, 2022). Buhalis (2020) and Hidayah and Suherlan (2020) suggested that the use of smart tourism destination concepts requires stakeholders that are interconnected with supportive technology platforms.…”
Section: Smart Tourism and Stakeholdersmentioning
confidence: 99%
See 3 more Smart Citations